NUMERICAL SIMULATIONS OF INTENSE PRECIPITATION IN MADEIRA ISLAND USING THE MESO-NH MODEL - Couto, Flavio (2012)
Extreme orographic precipitation events are a common cause of natural hazards such as flash floods, landslides, and avalanches in mountainous regions (Roe, 2005), and may be caused by different mechanisms. Situated in the Subtropical Atlantic Ocean (32º 45' N and 17º 00'W), Figure 1, the Madeira Island is the largest island of the Madeira Archipelago, with surface area of 737 km2, a length of 58 km, a 23 km width and a maximum altitude of 1861m (Pico Ruivo), consisting of a barrier elongated in the east-west direction (Prada et al., 2009) and presenting favorable conditions for generation or intensification of orographic precipitation, sometimes responsible by high records and several social-economical damages. During the winter 2009/2010, some events of heavy precipitation were observed in Madeira Island, mainly in high regions, as occurred on 22 December 2009, when intense rainfall was responsible for economic damages in isolated points of the island. On the other hand, in the last years, the use of highresolution simulations are becoming a common tool for diagnosis and prognosis of intense precipitation events around the world. Therefore, this study aims at analyzing the main aspects associated to the generation/enhancement of precipitation in Madeira Island, verifying the model's ability for the diagnostic of intense precipitation in a region where the orographic effects are predominant.